Outer nuclear layer recovery as a predictor of visual prognosis in type 1 choroidal neovascularization of neovascular age-related macular degeneration - Seungheon Lee; Kyung Tae Kim; Dong Yoon Kim; Ju Byung Chae; Eoi Jong Seo (Scientific Reports, 2023)
Abstract To investigate the changes in outer nuclear layer (ONL) thickness during anti-vascular endothelial growth factor (VEGF) treatment in type 1 choroidal neovascularization (CNV) and its impact on vision. Type 1 CNV eyes (n = 94) were retrospectively compared to normal control eyes (n = 35). Along with best-corrected visual acuity (BCVA), the location of CNV, foveal ONL thickness, and subretinal fluid height were measured using optical coherence tomography (OCT) and analyzed. Visual outcome and OCT biomarkers were compared. As a result, the CNV group had thinner foveal ONL and worse BCVA compared to the control group. ONL thickness recovered partially along with visual improvement following 3 monthly initial loading doses of aflibercept injections, and it correlated with the final BCVA during the 1-year follow-up. Eyes achieved foveal ONL recovery over + 10 µm had lower subfoveal CNV (45.5%) and showed better visual outcomes than eyes with stationary ONL or suboptimal ONL recovery (76.0%, p = 0.012). In conclusion, type 1 CNV eyes that recovered foveal ONL thickness at initial loading of anti-VEGF demonstrated good final visual outcome during the 1-year follow-up. Monitoring the foveal ONL thickness during early anti-VEGF treatment can give information about the visual outcomes in type 1 CNV.